Analisis Pengaruh Affective Commitment, Continuance Commitment Dan Normative Commitment Terhadap Kinerja Guru (Studi Kasus Representatif Guru SMK Muhammadiyah di Kabupaten Sragen) - Chikmah, Ririn Nur; , Muzakar Isa, SE, M.Si (2017)
This research analyzed the influence of affective, continuance, and normative commitment to the performance of Muhammadiyah Vocational High School teachers in Sragen Regency. The result is aimed at benefiting the improvement of teacher commitment and performance. The method used in this research is quantitative method with primary data. involving 75 teachers for the samples. The analysis tool in this research was data instrument analysis (validity and reliability test), classical assumption test (normality, multicollinearity, and heteroscedasticity test), and multiple linear regression (t, f, and R2 test). Based on T test result shows that affective commitment (X1) have positive and significant influence to teacher performance, while continuance commitment (X2) have positive but not significant influence to teacher performance, and normative commitment (X3) have positive and significant influence to teacher performance. Based on the F test, both affective, continuance, and normative commitment gave simultaneous influence to the teacher performance.